Augustyńska interpretacja sankcji za gniew (Mt 5, 22bc) na tle wczesnochrześcijańskiej egzegezy - Nieścior, Leon (Vox Patrum, 2024)
In Matthew 5:22, extremely harsh words against anger are addressed, in which certain sanctions are imposed for anger, depending on its three different manifestations. The author of article tries to systematise the collected references of the Greek and Latin Fathers to Mt 5:22bc, in which anger is subjected to a moral qualification. The article provides an overview of patristic thought on the subject. The author extracts St. Augustine’s thought on the subject and shows it against the background of the exegesis of other writers.